Find the difference quotient and simplify your answer. $\displaystyle f\left(x \right)={x}^{3}+x,\frac{f\left(x+h \right)-f\left(x \right)}{h},h\neq0$ Thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by Amy $\displaystyle f\left(x \right)={x}^{3}+x$ Then $\displaystyle f(x + h) = (x + h)^3 + (x + h).$ Now substitute and work with it, what do you get?
Originally Posted by Amy Find the difference quotient and simplify your answer. $\displaystyle f\left(x \right)={x}^{3}+x,\frac{f\left(x+h \right)-f\left(x \right)}{h},h\neq0$ Thanks Plug and chug Amy! $\displaystyle \frac{(x+h)^3+x+h-x^3-x}{h}=???$
O.K, O.K . I got Colby
View Tag Cloud